I have some problems with the verification of the third equation in Lemma 1 in this paper.

First of all, one has to notice that there is at least one Error in the Definition of $a_{\kappa,\nu}$ above. I think it must be $a_{\kappa,\nu} = \sum\limits_{j=0}^{f-1} \zeta_e^{2^{j+\nu}} a_{2^j\kappa} \sigma^j$ (that means the exponent of $\sigma$ has to be $j$, not $\nu$. Otherwise even the first equation of Lemma 1 makes no sense).

Another mistake one can find in the defintion of the involutory antiautomorphism $\ast$ on the second page of the paper. It has to be $(\rho^i \gamma)^\ast = c^i \rho^i \gamma^{-1}$ (that means the $s$ has to be replaced by $\rho$).

Now i want to give you a little summary of the general settings in the Situation of Lemma 1. Let $G$ denote the direct product of a cyclic group of order 2 with generator $\rho$ and the Group $G_0$ generated by elements $\sigma$ and $\tau$, which satisfy the relations $\sigma^f = 1, \tau^e = 1, \sigma^{-1} \tau \sigma = \tau^{q_0}$, where $f > 1$ is odd, $e = 2^f - 1, q_0 = 2^{f_0}, f_0 \geq 1$.

We consider the group algebra $\bar{\mathbb{F}}_2[G]$ and the involutory antiautomorphism $\ast$ on $\bar{\mathbb{F}}_2[G]$, defined by linearly extending the mapping $(\rho^i \gamma)^\ast = c^i \rho^i \gamma^{-1}$, where $i = 0,1; \gamma \in G_0; c \in \bar{\mathbb{F}}_2[G], c^2 = 1$.

The Element $a_{\kappa,\nu}$ of $\bar{\mathbb{F}}_2[G]$ is given by $a_{\kappa,\nu} = \sum\limits_{j=0}^{f-1} \zeta_e^{2^{j+\nu}} a_{2^j\kappa} \sigma^j = \sum\limits_{j=0}^{f-1} \zeta_e^{2^j(2^\nu - \kappa i)} \tau^i \sigma^j$ where $\zeta_e$ is a primitive root in $\mathbb{\bar{F}_2}$ which generates a normal basis of the extension $\mathbb{F}_2(\zeta_e)/\mathbb{F_2}$.

In order to proof equation 3 of Lemma 1, the author gives two auxiliary equations $a^\ast_{\kappa,\nu} = a_{e-\kappa, \nu}$ and $a_{\kappa,\nu} \cdot a_{\kappa'} = \left\{\begin{array}{ll} a_{\kappa, \nu}, & \kappa = \kappa' \\ 0, & \kappa \neq \kappa'\end{array}\right.$, but unfortunately i am not able to show only one of these equations.

Here my attempt for the first equation: We have $a^\ast_{\kappa,\nu} = \big(\sum\limits_{j=0}^{f-1} \sum\limits_{i=0}^{e-1} \zeta_e^{2^j(2^\nu - \kappa i)} \tau^i \sigma^j \big)^\ast = \sum\limits_{j=0}^{f-1} \sum\limits_{i=0}^{e-1} \zeta_e^{2^j(2^\nu - \kappa i)} (\tau^i \sigma^j)^{-1}$

and because of $\sigma^{-j}\tau^i\sigma^j = \tau^{i q_0^j}$ we obtain $\sum\limits_{j=0}^{f-1} \sum\limits_{i=0}^{e-1} \zeta_e^{2^j(2^\nu - \kappa i)} \tau^{-iq_0^j} \sigma^{-j}$

In the next step i have made indextransformations $i = -iq_0^{-j}$ and $j = -j$.

This leads to $\sum\limits_{j=0}^{f-1} \sum\limits_{i=0}^{e-1} \zeta_e^{2^{-j}(2^\nu + \kappa iq_0^j)} \tau^i \sigma^j = \sum\limits_{j=0}^{f-1} \sum\limits_{i=0}^{e-1} \zeta_e^{2^{-j}(2^\nu - (e - \kappa)iq_0^j)} \tau^i \sigma^j$.

But i have absolutely no clue why this should be the same as $a_{e-\kappa, \nu} = \sum\limits_{j=0}^{f-1} \sum\limits_{i=0}^{e-1} \zeta_e^{2^j(2^\nu - (e - \kappa)i)} \tau^i \sigma^j$.

Did i make a mistake or can anyone see what must be done to get the solution?


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Browse other questions tagged or ask your own question.